Feasibility of exclusive enteral feeds from birth in VLBW infants >1200 g – an RCT. (29th April 2013) - Sanghvi, Kishore P; Joshi, Pooja; Nabi, Fazal; Kabra, Nandkishor
Abstract Aim To evaluate the feasibility of initiation of exclusive enteral feeds on first day of life in very low birthweight infants >1200 g. Methods Haemodynamically stable infants with birthweights 1200–1500 g irrespective of gestational age were randomized into two groups. Study group: Enteral feeds 80 mL/kg/day started within 1 h of birth and increased by 20 mL/kg/day to 180 mL/kg/day. No intravenous fluids given. Control group: Intravenous fluids 50 mL/kg/day started along with enteral feeds 30 mL/kg/day within 1 h of birth and increased by 20 mL/kg/day to 180 mL/kg/day. The outcome measures were – primary: time to regain birthweight and secondary: duration of hospital stay, incidence of necrotizing enterocolitis and sepsis. Results Twenty three babies randomized in each group. Infants in study group regained birthweight earlier [mean 5.52 days, SD ± 2.94] compared to those in control group [mean 12.7 days, SD ± 2.25] (p < 0.0001). Duration of hospital stay was lower in study group [mean 15.04 days, SD ± 5.26] compared to those in control group [mean 28.04 days, SD ± 6.76] (p < 0.0001). No necrotizing enterocolitis detected. Conclusion It is feasible to initiate exclusive enteral feeds from first day of life in stable infants with birthweight between 1200 and 1500 g without any parenteral fluid support. It leads to twice as faster regaining of birthweight and halves duration of hospital stay.